PENDAMPINGAN PENGUATAN KESADARAN NASIONAL BERBASIS SEJARAH PADA SISWA INDONESIA DI SEKOLAH INDONESIA DAVAO, PHILIPINA - Merina Alie; Supandi Supandi; Ari Widayanti; Cahya Adhitya Pratama; Muhammad Restu Andhika (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service activity was carried out at the Davao Indonesia School, Philippines. As a school which consists of children of Indonesian descent, Davao Indonesia School has the responsibility of bringing students to know their country's origins and have the spirit of national awareness that they are the people of Indonesia. However, Davao Indonesia School has difficulties in activities because Davao Indonesia School does not yet have teachers with historical academic backgrounds. Therefore, the presence of community service activities by History lecturers really helps Davao Indonesia School in making activities with the theme of national awareness. History-based national awareness assistance for Indonesian Davao School students is assistance that includes activities (1) peer tutoring of historical material by FKIP Uhamka students (2) and public lectures on material about proclamation by history lecturers of FKIP Uhamka (3) Historical Story Telling by students. All activities are carried out within two days in the school on 09 and 11 August 2022. The enthusiasm of students in these activities can be seen during the story telling activity. In this activity, students enthusiastically said that they were Indonesians and were able to tell the meaning of struggle as a reflection of every historical event.